Pengaruh Pengaruh Perbedaan Jenis Pelarut Terhadap Kadar Fenolik Ekstrak Daun Sirsak (Annona Muricata L.): Pengaruh Perbedaan Jenis Pelarut Terhadap Kadar Fenolik Ekstrak Daun Sirsak (Annona Muricata L.) - Maria Dwi Ayu Listiawati; Kunti Nastiti; Mia Audina (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
Backgraund: Annona muricata L leaves are used as anticancer drugs by the public because Annona muricata L leaves have a high content of phenolic compounds that have antoxid activity that can ward off free radicals that cause cancer. Phenolic compounds have polar properties so that to obtain this compound the same polar solvents are used, namely ethanol 70%, ethanol 96% and Methanol where the use of different types of solvents will affect the resulting phenolic level. Objective: Knowing what are the levels and influences of differences in phenolic levels of leaves Annona Muricata L. leaves based on differences in solvent types Methods: This study used a pre-experimental method with a randomized design by conducting a maceration extraction method and then a Thin Layer Chromatography test was carried out to identify phenolic compounds. Then the determination of total phenolic levels using UV-Vis spectrophotometry. Results: Effect of differences in solvent type from phenolic levels with One Way ANOVA parametric test. The total phenolic content of Annona muricata L leaves of Ethanol extract was 70%, Ethanol 96% and Methanol obtained were 5,753 mg GAE/g, 4,022 mg GAE/g and 7,179 mg GAE/g. Differences in solvent type had a significant effect of 0,000 (p<0,05) on the phenolic levels of Annona Muricata L leaf extract. Conclusions: Based on the results of the study, it was concluded that methanol is effective in irradiating phenolics compared to other types of solvents.